Clinical effect of bronchial arterial infusion chemotherapy and CalliSpheres drug‐eluting beads in patients with stage II–IV lung cancer: A prospective cohort study. Issue 8 (30th June 2020) - Shang, Bin; Li, Jijun; Wang, Xingguang; Li, Daowei; Liang, Bin; Wang, Yonggang; Han, Xujian; Dou, Weitao; Chen, Gang; Shang, Jianqiang; Jiang, Shujuan
Abstract : Background: CalliSpheres are drug‐eluting beads used for tumor artery embolization, with clinical benefits in a number of cancer types. The aim of the study was to examine the clinical benefits and complications of patients with stage II–IV lung cancer treated with CalliSpheres drug‐eluting beads for embolization versus conventional vascular interventional treatment. Methods: This was a prospective cohort study conducted from August 2018 to May 2019. The patients were grouped according to traditional bronchial arterial infusion chemotherapy (infusion group) or bronchial arterial chemoembolization with CalliSpheres drug‐eluting beads loaded with adriamycin (CallisSphere group). Short‐term effects, serum tumor markers, and adverse reactions during follow‐up were compared between the two groups. Results: There were 60 participants enrolled into the study with 30 in each group including 54 men and six women, 42–78 years of age. In the CalliSphere group, compared with the infusion group, the disease control rate was 93.3% versus 73.3% ( P = 0.080) and the objective remission rate (ORR) was 86.7% versus 60.0% ( P = 0.039); the three‐ and six‐month progression‐free survival (PFS) and six‐month overall survival (OS) were better in the CalliSphere group (three‐month PFS: 96.7% vs. 73.3%, P = 0.026; six‐month PFS: 87.5% vs. 57.1%, P = 0.045; six‐month OS: 87.5% vs. 52.7%, P = 0.024); after treatment, the tumor markers in the CalliSphere group were lower (CEA: P < 0.001; CYFRA21‐1: P = 0.014). There were no differences in adverse reactions between the two groups. Conclusions: The clinical effect of bronchial arterial chemoembolization with drug‐eluting beads on lung cancer is probably significant and could improve the short‐term response, PFS, and OS in patients with stage IIIV lung cancer, without increasing severe adverse reactions. Key points: Significant findings of the study: The clinical effect of bronchial arterial chemoembolization with drug‐eluting beads on lung cancer is probably significant and could improve the short‐term response, PFS, and OS in patients with stage II–IV lung cancer, without increasing severe adverse reactions. What this study adds: The ORR, PFS, OS was better in the CalliSphere group than that of infusion group; CEA and CYFRA21‐1 were significant lower in CalliSphere group.